No Effect of Microgravity and Simulated Mars Gravity on Final Bacterial Cell Concentrations on the International Space Station: Applications to Space Bioproduction - Santomartino, Rosa; Waajen, Annemiek C.; de Wit, Wessel; Nicholson, Natasha; Parmitano, Luca; Loudon, Claire-Marie; Moeller, Ralf; Rettberg, Petra; Fuchs, Felix M.; Van Houdt, Rob; Finster, Kai; Coninx, Ilse; et al. (Frontiers in Microbiology, 2020)
Microorganisms perform countless tasks on Earth and they are expected to be essential for human space exploration. Despite the interest in the responses of bacteria to space conditions, the findings on the effects of microgravity have been contradictory, while the effects of Martian gravity are nearly unknown. We performed the ESA BioRock experiment on the International Space Station to study microbe-mineral interactions in microgravity, simulated Mars gravity and simulated Earth gravity, as well as in ground gravity controls, with three bacterial species: Sphingomonas desiccabilis, Bacillus subtilis and Cupriavidus metallidurans. To our knowledge, this was the first experiment to study simulated Martian gravity on bacteria using a space platform. Here, we tested the hypothesis that different gravity regimens can influence the final cell concentrations achieved after a multi-week period in space. Despite the different sedimentation rates predicted, we found no significant differences in final cell counts and optical densities between the three gravity regimens on the ISS. This suggests that possible gravity-related effects on bacterial growth were overcome by the end of the experiment. The results indicate that microbial-supported bioproduction and life support systems can be effectively performed in space (e.g. Mars), as on Earth.